A study of wheat-weed response and economical analysis to fertilization and post-emergence herbicides under arid climatic conditions - Sarita,; Singh, Ishwar; Mehriya, Moti Lal; Samota, M. K. (Frontiers in Agronomy, 2022)
A two-year field experiment was conducted in two consecutive rabi seasons under arid climatic conditions to examine the effect of different fertility levels and herbicides on weed dynamics and the performance of wheat (Triticum aestivum L.). Results revealed that a significantly minimum weed dry weight was recorded with 75% RDF (Recommended Dose of Fertilizer) (90-30 kg N-P2O5/ha). Application of 100% RDF (120-40 kg N-P2O5/ha) recorded significantly higher weed dry weight at 35 DAS (Days After Sowing) (16.50 g/m2) and harvest (28.15 g/m2), growth and yield attributes i.e. plant height (89.14 cm), crop dry matter accumulation (300.8 g/meter row length), crop growth rate (17.08 g/m2/day), leaf area index at 50 DAS (3.06, net assimilation rate 50-75 DAS, length of the spike (13.36 cm), number of grains/spike (41.52), grain yield (4083 kg/ha), straw yield (5019 kg/ha) and biological yield (9103 kg/ha) over 75% RDF. This treatment remains at par with 125% RDF (150-50 kg N-P2O5/ha) except for leaf area index at 75 DAS. Among the herbicidal treatments, application of ready to use herbicides clodinafop-propargyl 15% + metsulfuron methyl 1% @ 64 g/ha gave the superior value of weed indices i.e. higher weed control-efficiency (91.30), crop resistance-index, and herbicide efficiency-index, and lower weed-index (1.91) over other herbicides. This treatment also exhibited significantly higher plant height (92.33 cm), crop dry matter accumulation (325.5g/meter row length), crop growth rate ( 16.49 g/m2/day), leaf area index (3.15), net assimilation rate, length of the spike (14.28 cm), number of spike/meter row length (153.0), number of grains/spike (44.52), grain yield (4374 kg/ha), straw yield (5381 kg/ha) and biological yield (9755 kg/ha) over weedy check plot, which was followed by sulfosulfuron 75% + metsulfuron methyl 5% @ 32 g/ha, both of which remained statistically at par with each other except the number of grains/spike. The application of 100% RDF and clodinafop-propargyl 15% + metsulfuron methyl 1% @ 64 g/ha recorded higher net returns and maximum B: C ratio.